Chronic Noise Exposure with Normal Hearing is Related to Adverse Quality of Life and Burnout - Christos Karaiskos; Ioannis Vlastos; Georgios Farantos; Georgios Rachiotis; Effie Simou; Georgios Dounias (European Scientific Journal, ESJ, 2025)
Aims and scope: Occupational noise exposure is a well-known factor of hearing loss and other health-related problems. Its contribution to burnout and health-related quality of life, particularly when there is no hearing loss is less well studied. Herein we aim to study the effect of noise on the responses of normal-hearing industrial workers on validated instruments. Methods: 384 industrial workers from three pharmaceutical companies with normal hearing were stratified into two groups: a noise-exposure group (n=195) and a non-exposure group (n=125). In addition to basic demographic characteristics, factors such as smoking, and BMI were examined alongside responses to the Oldenburg Burnout Inventory (OLBI) and SF-36 questionnaire. Findings: The noise-exposure group exhibited a higher prevalence of smokers (p<0.01), a slightly elevated median BMI (p=0.04), and reported more pronounced exhaustion as measured by the OLBI (p=0.03). Furthermore, they exhibited poorer responses in various dimensions of the SF-36 questionnaire, particularly in bodily pain (p<0.01), physical functioning (p=0.03), physical role functioning (p=0.02), and emotional role functioning (p<0.01) scales. Conclusion: Occupational noise exposure, even in the absence of hearing loss, is associated with a higher prevalence of burnout symptoms and an overall reduced health-related quality of life among industrial workers. These insights underscore the need for proactive measures to mitigate noise exposure's adverse impact on employee well-being and productivity in noisy work environments, independently of the findings in their audiometric results.